Evaluation of Factors Present During Labor Stress - López-Mena, Luis; Campos Alvarez, Javier (Revista de Psicología, 2002)
Stress has been defined as an interactive construct. It constitutes the reaction of a person both at a physiological and psychological level, when confronting a stimulus configured by the interaction of individual, environmental and social factors, leading to an adaptation or an imbalance of the organism. Departing from this definition which globalizes the theoretical perspective on the matter, this study constitutes an analysis of stress mechanisms through the evaluation of five variables: a) perceived stress; b) perception of family social support; c) perception of friends’ social support; d) the level of stress generated by worries or life events. These variables were studied in a group of 107 workers presenting a high index of accidents, belonging to an important mining company of Chile. Analysis of results was done through descriptive and correlated procedures. The first was oriented at determining stress levels and its associated variables in the sample studied. The correlational analysis has as its objective to determine the degree of existing relationship among the variables and how these are associated with stress. The main conclusions are: a) the quality of a battery of scales undergoing an exhaustive statistical analysis; b) the presence of significant levels of stress and the associated variables in the sample being evaluated and c) the presence of statistically significant correlations among the evaluated variables. From the analysis of variables, key factors are extracted to be considered as points of departure for future programs of intervention in stress management of workers.